Effect of Ni-doping on the electronic bandgap and thermal conductivity of calcium hydroxide: Experimental and theoretical investigation - Basit Ali; Aamir Khan; Faheem Amin (Results in Physics)
In the current research work, pure and nickel-doped calcium hydroxide (Ni-doped Ca(OH)2) were studied both experimentally and theoretically. Theoretically, the material is examined by using the full-potential linearized augmented plane wave (FP-LAPW) scheme as implemented in the WIEN2K Simulation package. Experimentally, the pure and Ni-doped Ca(OH)2 were prepared via a simple inexpensive chemical method. The structural, thermal, electronic, and optical behavior of doped and pure Ca(OH)2 were analyzed. The addition of nickel increased the experimental thermal conductivity from 0.0942 to 0.2063 W/mK. The experimental band gap energy was determined to reduce from 5.21 eV to 4.04 eV for pure and Ni-doped Ca(OH)2 respectively. The Ni-doped Ca(OH)2 sample shows an increasing trend of optical properties in the visible region by incorporating Ni+2 ions. This research work shows that Ni-doped Ca(OH)2 is a favorable competitor for enhanced thermoelectric and optoelectronic applications.